The British Collier in British Columbia: Another Archetype Reconsidered - Belshaw, John (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1994)
It is a widely held axiom of British Columbia's labour history that the province's radical tradition originated among immigrant British workers who formed the social bedrock of Vancouver Island's coaltowns in the 19th century. This paper challenges the stereotype of the British BC worker in the last century by balancing the post-immigration experience against the pre-emigration vocabulary of work, class, race, and politics. I conclude that insofar as a British fountainhead is significant for BC's political history it is in the diffusion of class solidarity to competing claimants for political support. The legacy of the British collier on Vancouver Island was not one of monolithic radicalism or even Labourism; instead it was one of conflicting inclinations which were as politically divisive for labour in Britain as they were on Canada's west coast.